Role of bacteria and microbial metabolites in immune modulation during early life - Oldereid, Tine Simensen; Jiang, Xiaojun; Nordhus, Kathrine Sivertsen; Ponzetta, Andrea; Bjørnholt, Jørgen Vildershøj; Björkström, Niklas K.; Melum, Espen; Rasmussen, Henrik (Scandinavian journal of immunology, 2024)
Host–microbiome interplay from birth is essential for immune imprinting and tuning. Live gut microbes and microbial‐derived metabolites regulate the development and modulation of the immune system, but whether microbial metabolites solely are sufficient to induce immune maturation remains unclear. Sterile faecal filtrates (FFT) were generated from murine gut contents. Newborn germ‐free (GF) mice were treated twice daily with FFT (GF‐FFT) or saline (GF‐NaCl) from post‐natal day 5 until 4 weeks of age. A third group of GF neonates were conventionalized by the transfer of caecal microbiota with live gut microbes. Host immune compartments were comprehensively immunophenotyped and systemically analysed in all available immune‐related organs using flow cytometry. Oral FFT was associated with reduced survival among neonates (n = 7/19; 36.8% mortality), while saline treatment was well tolerated (n = 1/17, 5.9% mortality). Four‐week‐old FFT‐treated pups were comparable in body weight to GF‐NaCl, and the major B‐cell, conventional T‐cell and unconventional T‐cell subsets were unchanged from saline‐treated mice. Live bacteria administered during early life induced clear changes in proportions of B cells, T cells and T‐cell subsets in all mucosal tissues and secondary lymphoid organs compared to GF‐FFT, including restoration of intestinal natural killer T (NKT) cells with characteristics similar to conventional pups. Our findings show that oral administration of a FFT made of microbial metabolites, antigens and bacteriophages alone is insufficient to induce normal immune development elicited by the presence of live bacteria. Reduced survival during neonatal FFT treatment suggests a potential bioactive attribute of sterile faecal filtrates. The immunomodulatory impact of microbial metabolites and by‐products during early life remains largely elusive. This study demonstrates that live bacteria are needed for normal immune development. Oral treatment with bacteria‐free faecal filtrates in germ‐free mice is insufficient to shape the immune system as elicited by the presence of a microbiota.